(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Anaemia has been recognized to be one of the most common disorders mainly found in women. The biological cause of anaemia is because of the deficiency of iron in the body. Not only this, but the test results of anaemia shows that along with the deficiency of iron in the whole body, there occur inabilities in an adequate supply in the appropriate amount of iron in the body, which is mostly consumed by the bone marrow. The dysfunction occurs in the body when bone marrow finds a lack of iron in the body to consume and produce a sufficient amount of red blood cells for the maintenance of the oxygenation process of the tissues within the body. From the biological studies, it has been estimated that a liver peptide hormone called “hepcidin” is controlling the viability of iron. Anaemia has been a global health problem that is mainly associated with the young children and pregnant women.